2019
DOI: 10.1088/2053-1591/ab56d6
|View full text |Cite
|
Sign up to set email alerts
|

Absorption enhancement by transition metal doping in ZnS

Abstract: Transition metal doping is an effective tool for controlling optical absorption in ZnS and hence the number of photons absorbed by photovoltaic devices. By using first principle density functional calculations, we compute the change in number of photons absorbed upon doping with a selected transition metal and found that Ni offers the best chance to improve the performance. This is attributed to the formation of defect states in the band gap of the host ZnS which give rise to additional dipole-allowed optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Metal doping is an effective tool for controlling the optical absorption in the GaSb material and hence the photons absorbed by the photonic devices. [ 31 ] In our study, we found that Ge and Zn doping shows the best chance to improve performance because dipole active states are formed in the bandgap of GaSb.…”
Section: Resultsmentioning
confidence: 81%
“…Metal doping is an effective tool for controlling the optical absorption in the GaSb material and hence the photons absorbed by the photonic devices. [ 31 ] In our study, we found that Ge and Zn doping shows the best chance to improve performance because dipole active states are formed in the bandgap of GaSb.…”
Section: Resultsmentioning
confidence: 81%
“…N, P, and As for p-type ZnS nanocrystals [151] Ni, Mn, Cu, Al for ZnS [152][153][154][155][156] colloidal Mn for CdS/ZnS, CdZnS QDs [157,158]. Fe for ZnS, CdTe, CdMnTe, ZnCdTe [159]. Mn for ZnSe nanocrystals [160].…”
Section: Doping Of Ii-vi Semiconductors and Compoundsmentioning
confidence: 99%
“…12 By doping or substituting Zn with Mn, the photon absorption efficiency is improved, which together with a lowering of the band gap favors photocatalytic degradation under visible light. 4,6,7 Furthermore, Mn doping creates trap states, which prolong the electron−hole recombination time. 4,7,12,13 Three polymorphs of ZnS have been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4,6,7 Furthermore, Mn doping creates trap states, which prolong the electron−hole recombination time. 4,7,12,13 Three polymorphs of ZnS have been reported. Sphalerite is the stable allotrope under ambient conditions, while wurtzite is stable at high temperatures.…”
Section: ■ Introductionmentioning
confidence: 99%